Web engineering: principles and techniques - Suh, Woojong (IDEA Group Publishing, 2005)
Web engineering: principles and techniques provides clarity to this often complicated issue. Covering a wide range of topics such as: basic perspectives on web engineering, development methodologies for web applications, web metrics and quality models, web resource management techniques and standards, maintenance and evolution methods for web applications, and web intelligence techniques and models, this book provides the necessary tools vital for organizations to utilize the full potential of web engineering.